ANALISIS KEBUTUHAN AIR BERSIH DOMESTIK DESA MARENGAN LAOK KECAMATAN KALIANGET KABUPATEN SUMENEP - Ach. Desmantri Rahmanto; Nor Zainah (Fakultas Teknik, Universitas Wiraraja, 2026)
Marengan Laok Village is one of the villages in Sumenep Regency which is included in the category of densely populated settlements and coastal areas surrounded by salt fields and the Madura Strait. Divided into 4 hamlets, namely Karang Komis Hamlet, Beddi Hamlet, Jenengan Hamlet, and Masjid Hamlet) with the main source of drinking water and clean water needs of the community relying on the services of the Sumenep Regency Regional Drinking Water Company (PDAM). The purpose of this study is to determine the domestic clean water needs of the Marengan Laok Village community for the next 5, 10, 15, 20 and 25 years. The data analysis technique used in this study is the projection of the number of customers up to 25 years and the projection of the amount of water needs up to 25 years. The need for domestic clean water in Marengan Laok Village for the next 5 years is 0.54167 l/second, for the next 10 years it is 0.65856 l/second, for the next 15 years it is 0.77662 l/second, for the next 20 years it is 0.89352 l/second, and for the next 25 years it is 1.01042 l/second. The estimated need for domestic clean water discharge production for the next 5 years is 7,719 l/day, for the next 10 years it is 9,335 l/day, for the next 15 years it is 10,955 l/day, for the next 20 years it is 12,571 l/day, and for the next 25 years it is 14,190 l/day.